The ectopic adrenocorticotropic hormone syndrome in carcinoid tumors - Fazel, Poorya (Baylor Health Care System, 2008)
Ectopic production of adrenocorticotropic hormone by carcinoid tumors is relatively uncommon and may not be recognized by physicians. This report describes a woman who had Cushing syndrome from the ectopic secretion of adrenocorticotropic hormone by a carcinoid tumor. Her cause of death was a pneumonia that may have been secondary to her untreated hypercortisolism. There are threeinstructive elements of this case: 1) the recognition of Cushing syndrome, 2) the association of Cushing syndrome with low-grade (carcinoid tumors) as well as with high-grade (small cell carcinoma) neuroendocrine tumors, and 3) the need to treat the hypercortisolism as well as the tumor.